Biochemical Profiling of Saliva and Gingival Crevicular Fluid in Peri-Implant Mucositis: A Focus on Bone Metabolism, Oxidative Stress, and Matrix Remodeling: Biochemical Profiling of Peri-Implant Fluids - Wan, Huiqian; Wang, Ying (Journal of Medical Biochemistry, 2026)
Background: Peri-implant mucositis involves coordinated disturbances in bone metabolism, oxidative stress, and matrix remodeling, but these pathways are rarely assessed jointly in saliva and gingival crevicular fluid (GCF). This study aimed to establish a quantitative biomarker profile in peri-implant health and peri-implant mucositis and to compare the detection value of the two fluids. Methods: This single-center retrospective study included 64 patients with peri-implant health and 71 patients with peri-implant mucositis who were enrolled between August 2024 and December 2025. Saliva and GCF samples were collected. Basic biochemical parameters were measured using an automated biochemical analyzer. More than 30 biochemical biomarkers, including OCN, CTX-I, MDA, 8-OHdG, MMP-8, MMP-9, MPO, and NE, were quantitatively assessed using double-antibody sandwich enzyme-linked immunosorbent assay (ELISA), competitive ELISA, colorimetric assays, and fluorogenic substrate assays. Laboratory quality control was applied throughout sample testing. Results: Compared with saliva, GCF showed more pronounced biomarker alterations in the mucositis group, with most GCF biomarker changes being approximately 1.5- to 3.0-fold greater than the corresponding salivary changes; MPO and NE increased by more than 2.5-fold, suggesting that GCF more sensitively reflected local microenvironmental disruption. Markers of bone metabolism indicated a negative balance, with decreased bone formation markers, including osteocalcin (OCN), bone-specific alkaline phosphatase (BALP), and N-terminal propeptide of type I procollagen (PINP), and increased bone resorption markers, including C-terminal telopeptide of type I collagen (CTX-I), tartrate-resistant acid phosphatase 5b (TRAP-5b), and cathepsin K (CTSK) (P<0.05). Oxidative damage products, including malondialdehyde (MDA) and 8-hydroxy-2’-deoxyguanosine (8-OHdG), increased simultaneously, whereas antioxidant enzyme activities and reduced glutathione (GSH) levels decreased (P<0.05). Matrix metalloproteinase-8 (MMP-8) and matrix metalloproteinase-9 (MMP-9) activities showed the most marked increases. Matrix components, including hyaluronic acid (HA), laminin (LN), and fibronectin (FN), were reduced, while collagen degradation products were elevated (P<0.05). Neutrophil-specific inflammatory markers, including myeloperoxidase (MPO) and neutrophil elastase (NE), increased by more than 2.5-fold (P<0.05). The intra-assay and inter-assay coefficients of variation and sample recovery rates of all detection methods met clinical laboratory standards. Conclusion: The combined biomarker panel revealed coordinated biochemical disruption in peri-implant mucositis, and GCF showed greater sensitivity than saliva in reflecting local microenvironmental changes, supporting its use in early non-invasive laboratory monitoring.